2009
DOI: 10.1007/s10295-009-0661-5
|View full text |Cite
|
Sign up to set email alerts
|

High-yield fermentative preparation of tetramethylpyrazine by Bacillus sp. using an endogenous precursor approach

Abstract: A spore-forming Bacillus sp. was isolated from a high-temperature Daqu, a starter culture of Chinese Maotai-flavor liquor, using an endogenous precursor screening strategy. The Bacillus sp. was capable of producing a high level of 2,3,5,6-tetramethylpyrazine (TTMP) via a precursor of 3-hydroxy-2-butanone (HB). The strain was characterized as Bacillus subtilis based on morphological, physiological, and biochemical properties as well as on partial 16S rRNA gene sequences. Different carbon and nitrogen sources as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 27 publications
4
75
0
Order By: Relevance
“…Additionally, another B. subtilis isolate showed the ability to produce tetramethylpyrazine (a commonly occurring alkylpyrazine that is responsible for the odor of oriental foods, such as Chinese liquors) via the precursor 3-hydroxy-2-butanone (33). Combined with the findings of the present study, this suggests that Bacillus isolates can convert aromatic precursors and influence flavor formation (34,35).…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, another B. subtilis isolate showed the ability to produce tetramethylpyrazine (a commonly occurring alkylpyrazine that is responsible for the odor of oriental foods, such as Chinese liquors) via the precursor 3-hydroxy-2-butanone (33). Combined with the findings of the present study, this suggests that Bacillus isolates can convert aromatic precursors and influence flavor formation (34,35).…”
Section: Discussionsupporting
confidence: 74%
“…One of them was centrifuged (10,0009g, 10 min) and the precipitate was collected, washed twice with distilled water and dried at 105°C to constant weight to determine the biomass of the culture according to Ji et al [12], the supernatant was used to determine total sugar using 3,5-dinitrosalicylate method as described by Miller [13]. Another aliquot was diluted to appropriate folds with phosphate buffer (0.5 M, pH 7.0), the dilution was then assayed for precursor HB and TTMP according to the literature [10].…”
Section: Methodsmentioning
confidence: 99%
“…strains [5][6][7]10], and kinds of methods were accordingly developed for enhanced TTMP production, such as enrichment of the medium with precursor 3-hydroxy-2-butanone (HB) [6,7], the employment of soytone and vitamin supplements [5] and accumulation of precursor HB endogenously from glucose [10]. However, little work has concentrated on the prominent effect of inorganic nitrogen source, such as ammonium salt on cell growth, precursor HB accumulation and corresponding TTMP production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Recently, a high-yield strain of 2,3,5,6-tetramethylpyrazine was found in Chinese daqu, which showed that some pyrazines could be derived from the microbial products. 18 Six acids were identified in this work, the most abundant of which was butanoic acid, followed by hexanoic acid. These acids were produced by a diversity of microorganisms during fermentation of Chinese liquor.…”
Section: Sbse and Gc-ms Quantificationmentioning
confidence: 98%